The impact of trade openness on global carbon dioxide emissions: Evidence from the top ten emitters among developing countries - Ertugrul, Hasan Murat; Cetin, Murat; Seker, Fahri; Dogan, Eyup (ELSEVIER, 2016)
This study aims to analyze the relationship between carbon dioxide (CO2) emissions, trade openness, real income and energy consumption in the top ten CO2 emitters among the developing countries; namely China, India, South Korea, Brazil, Mexico, Indonesia, South Africa, Turkey, Thailand and Malaysia over the period of 1971-2011. In addition, the possible presence of the EKC hypothesis is investigated for the analyzed countries. The Zivot-Andrews unit root test with structural break, the bounds testing for cointegration in the presence of structural break and the VECM Granger causality method are employed. The empirical results indicate that (i) the analyzed variables are co-integrated for Thailand, Turkey, India, Brazil, China, Indonesia and Korea, (ii) real income, energy consumption and trade openness are the main determinants of carbon emissions in the long run, (iii) there exists a number of causal relations between the analyzed variables, (iv) the EKC hypothesis is validated for Turkey, India, China and Korea. Robust policy implications can be derived from this study since the estimated models pass several diagnostic and stability tests. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Trade openness; Energy consumption; Carbon dioxide emissions; Climate change; Environmental Kuznets curve hypothesis; Bounds test for cointegration; ENVIRONMENTAL KUZNETS CURVE; FOREIGN DIRECT-INVESTMENT; RENEWABLE ENERGY-CONSUMPTION; CO2 EMISSIONS; ECONOMIC-GROWTH; FINANCIAL DEVELOPMENT; ELECTRICITY CONSUMPTION; COAL CONSUMPTION; INTERNATIONAL-TRADE; CAUSALITY ANALYSIS; Biodiversity & Conservation; Environmental Sciences & Ecology